1998
DOI: 10.1007/s004490050540
|View full text |Cite
|
Sign up to set email alerts
|

Influence of impeller type on mass transfer in fermentation vessels

Abstract: Radial¯ow Rushton impellers were compared qualitatively with axial¯ow hydrofoil impellers (Max¯o T and A315) at the pilot scale. Six types of impellers were compared for qualitative differences in mass transfer. Measurements were conducted using three model systems: water, glycerol and Melojel (soluble starch). Power measurements were obtained using watt transducers, which although limited in accuracy and prone to interferences, were able to provide useful qualitative monitoring results. While there was little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Low-power Prochem ® hydrofoil impellers were used to enhance fluid circulation in the reactor. Prochem hydrofoils have been evaluated for use in bioreactors in the past, but mostly only in the conventional baffled stirred tank configuration [16][17][18][19][20]. A few studies have been reported in reactors with axial flow marine propellers inside draft-tubes, but only in relatively small (≤250 l) vessels [6,11,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Low-power Prochem ® hydrofoil impellers were used to enhance fluid circulation in the reactor. Prochem hydrofoils have been evaluated for use in bioreactors in the past, but mostly only in the conventional baffled stirred tank configuration [16][17][18][19][20]. A few studies have been reported in reactors with axial flow marine propellers inside draft-tubes, but only in relatively small (≤250 l) vessels [6,11,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…15-20 % of all operating costs. Thus, any such improvements can have a large influence on process economics [34]. This strategy of step-wise DO control was found to be economical in terms of power and oxygen consumption accompanied by lower foaming problems and better process control, while at the same time yielding a higher specific productivity (6.866 units/L h -1 ) compared to the other runs, as seen from the data in Tab.…”
Section: Effect Of Varying Dissolved Oxygen (Do) Concentrationsmentioning
confidence: 80%
“…It was also noticed that by increasing the superficial gas velocity, very close values of k L a were obtained for the two types of radial impellers used. Comparative studies with RT and A315 impellers in cultures of Streptomyces in a stirred bioreactor revealed that the k L a value increases by 50% with the use of RT impellers [16]. Other studies using a stirred reactor and water as the fluid model found that RT impellers present k L a values up to 40% higher, compared to the A315 impellers [14]; our studies confirmed that even with a stirred hybrid airlift bioreactor, the use of radial impeller favors the k L a increase.…”
Section: B Volumetric Oxygen Transfer Coefficientmentioning
confidence: 99%